1985
DOI: 10.2307/1938028
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance History and Serotiny of Pinus contorta in Western Montana

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Sun, Abstract. Mature Pinus contorta var. latifolia in the Bitterroot watershed of western Montana bear either predominantly ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…Muir and Lotan (47) found that the frequency of serotiny in lodgepole pine was most strongly related to the type of disturbance that initiated a stand, with fire-initiated stands being much more serotinous than other stands. This suggests the potential for very rapid change in the frequency of serotiny (i.e., a single fire interval), and that high frequencies of stand-replacing fire should result in high frequencies of serotiny (because most stands will have initiated due to a stand-replacing fire).…”
Section: Discussionmentioning
confidence: 99%
“…Muir and Lotan (47) found that the frequency of serotiny in lodgepole pine was most strongly related to the type of disturbance that initiated a stand, with fire-initiated stands being much more serotinous than other stands. This suggests the potential for very rapid change in the frequency of serotiny (i.e., a single fire interval), and that high frequencies of stand-replacing fire should result in high frequencies of serotiny (because most stands will have initiated due to a stand-replacing fire).…”
Section: Discussionmentioning
confidence: 99%
“…9). The sub-model is based on previously published principles and equations (Muir and Lotan 1985, Greene and Johnson 1994, 1998Gauthier et al 1996, Charron and Greene 2002, Calogeropoulos et al 2003, Radeloff et al 2003 and is applied to determine both in situ (from propagules that come from the cell itself) and ex situ (from propagules that come from neighbouring cells) regeneration. Modifications were brought to these equation systems based on the work of Hogg and Schwartz (1997), in order to take GCC into account.…”
Section: The Natural Regeneration Sub-modelmentioning
confidence: 99%
“…2-12), and geographically. A high degree of cone serotiny is likely to occur where there are large, stand-replacement fires; relatively short, fire-free intervals; and fire sizes large enough to limit seed dispersal from unburned areas (Muir and Lotan 1985;Parker and Kelly 1989).…”
Section: Seedbankmentioning
confidence: 99%